CXCL14 Maintains hESC Self-Renewal through Binding to IGF-1R and Activation of the IGF-1R Pathway - Chih-Lun Cheng; Shang-Chih Yang; Chien-Ying Lai; Cheng-Kai Wang; Ching-Fang Chang; Chun-Yu Lin; Wei-Ju Chen; Po-Yu Lin; Han-Chung Wu; Nianhan Ma; Frank Leigh Lu; Jean Lu (Cells, 2020)
Human embryonic stem cells (hESCs) have important roles in regenerative medicine, but only a few studies have investigated the cytokines secreted by hESCs. We screened and identified chemokine (C-X-C motif) ligand 14 (CXCL14), which plays crucial roles in hESC renewal. CXCL14, a C-X-C motif chemokine, is also named as breast and kidney-expressed chemokine (BRAK), B cell and monocyte-activated chemokine (BMAC), and macrophage inflammatory protein-2γ (MIP-2γ). Knockdown of CXCL14 disrupted the hESC self-renewal, changed cell cycle distribution, and further increased the expression levels of mesoderm and endoderm differentiated markers. Interestingly, we demonstrated that CXCL14 is the ligand for the insulin-like growth factor 1 receptor (IGF-1R), and it can activate IGF-1R signal transduction to support hESC renewal. Currently published literature indicates that all receptors in the CXCL family are G protein-coupled receptors (GPCRs). This report is the first to demonstrate that a CXCL protein can bind to and activate a receptor tyrosine kinase (RTK), and also the first to show that IGF-1R has another ligand in addition to IGFs. These findings broaden our understanding of stem cell biology and signal transduction.